Implementation of Lean in the function of production optimization: Problem framework - Stojanović Željko V. (Savez inženjera i tehničara Srbije, 2021)
The paper deals with the discussion of the value framework for the implementation of the Lean philosophy in the function of achieving the optimal level of business of the organization. By systematizing the literature data, the paper provides a basic insight into the thoughts, ideas and attitudes of the Lean approach, observing it inevitably in the context of factors that affect the success of its implementation in manufacturing industries. Identifying the problem framework in which the idea of Lean philosophy is realized is one of the most critical aspects that helps organizations to identify and eliminate weaknesses of the industrial system by applying certain tools and techniques that will enable a more successful outcome of implementation of this methodology whose principles can improve company performance. The discussion of the basic methods of the Lean approach was conducted in a way that allows considering of the practical contribution of the methods in correlation with Lean as the basic strategy. The results of the research showed the existence of a wide range of complex phenomena at the level of the entire organization, which are in mutual interaction and which, by their action, hinder the certainty of the success of Lean implementation by applying pre-tested tools and methods.